Anti-Inflammatory Activity of Rg3-Enriched Korean Red Ginseng Extract in Murine Model of Sepsis. (11th October 2018) - Saba, Evelyn; Jeong, Dahye; Irfan, Muhammad; Lee, Yuan Yee; Park, Sang-Joon; Park, Chae-Kyu; Rhee, Man Hee
Abstract : Ginseng has therapeutic effects on various bodily disorders ranging from minor inflammation to major cardiovascular diseases. In our study, we explored the anti-inflammatory effects of Rg3-enriched red ginseng extract (Rg3-RGE), a ginsenoside belonging to the panaxadiol group. We employed nitric oxide assay (NO) and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR), western blot, and hematoxylin and eosin staining (H&E) to elucidate the anti-inflammatory activity of Rg3-RGE. Rg3-RGE potently suppressed NO production in the murine macrophage cell line, RAW 264.7 cells, without any cytotoxicity across dosages. Additionally, it inhibited the mRNA expression of proinflammatory mediators and cytokines like iNOS, COX-2, IL-1 β, IL-6, and TNF- α . Moreover it also inhibited the levels of malondialdehyde levels in serum of septic shock mice. Immunoblot analysis showed that Rg3-RGE induced anti-inflammatory signal transduction via the NF- κ B and MAPK pathways. A remarkable attenuation of inflammation by oral treatment with Rg3-RGE in mice was observed in the survival study. The in vivo study using a septic shock mouse model also showed similar results as the in vitro study. Our findings suggest that Rg3-RGE can potentially be a potent anti-inflammatory agent that likely mediates its anti-inflammatory effects via the NF- κ B and MAPK pathways.